FOOT POSTURE AND ITS RELATIONSHIP WITH KNEE KINEMATICS IN BAREFOOT RUNNING OF THE HEALTHY ADULT. Issue 4 (1st February 2017) - Wong, Trina; Paton, Bruce
Abstract : Background: Abnormal dynamic knee moments and variations of static foot posture are risk factors for chronic lower limb injury development. However, relationships between the two have yet to be established in the running gait. Objective: The primary aim was to investigate the correlation between variations in static foot posture and maximum knee adduction. Secondary aims investigated the correlation of static foot posture with variables that affected dynamic knee motion. Design: A single-group prospective exploratory study design was implemented. Setting: Laboratory-based study setting. Participants: 23 volunteers from University College London social media network(n=3119) recruited in June 2016 met entry criteria of healthy adult 18–59 years) with no lower limb musculoskeletal injury in the last 6 months, history of biomechanical abnormality(including use of prosthesis) or lower limb surgery. All participated and completed study but only 14 sets of data were included due to data-corruption. An a priori sample size calculation determined that 9–14 participants were required to demonstrate significantly different correlations(α=0.05, β=0.20). Assessment of Risk Factors: Foot Posture Index scores of each participant's dominant foot was an independent variable during a 13 minute barefoot treadmill gait analysis. Main Outcome Measurements: Maximum knee adductor moments, knee tri-planar kinematics, hip tri-planar kinematics, maximum loading force and foot-strike pattern were measured at 3 instances(1.39 m/s; 3.6 m/s; self-selected running speed) as determined prior to data-collection. Results: No significant correlation (p<0.05) was found between static foot posture measurements and all outcome variables once confounders were accounted for. When comparing maximum knee adductor moments between the 3 speeds, significant correlations were observed (r=0.66–0.71, p<0.01). Conclusions: In the healthy population, static foot posture and dynamic knee motion demonstrate a poor and insignificant relationship. Dynamic motion should be assessed independently in predicting future injury where more evidence is needed to account for variations in knee adductor moments.